2017
DOI: 10.1007/s00330-017-4899-4
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of high-frequency power-based diffusion-weighted imaging in prediction of neuroepithelial tumour grading

Abstract: • HFP shows positive correlation with neuroepithelial tumour grading. • HFP presents a good diagnostic efficacy for LGG and HGG. • HFP is helpful in the selection of brain tumour boundary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A meta-analysis showed that the quantitative measurement of the apparent diffusion coefficient (ADC) value can be used to grade gliomas with high accuracy ( 9 ). Our previous study demonstrated that the minimum ADC (ADCmin) can be used to predict the grading of neuroepithelial tumors ( 10 ). Prior studies ( 11 , 12 ) have shown that the characteristics of lesions, such as location, internal structure, and enhancement pattern, are different among the genetic subtypes of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis showed that the quantitative measurement of the apparent diffusion coefficient (ADC) value can be used to grade gliomas with high accuracy ( 9 ). Our previous study demonstrated that the minimum ADC (ADCmin) can be used to predict the grading of neuroepithelial tumors ( 10 ). Prior studies ( 11 , 12 ) have shown that the characteristics of lesions, such as location, internal structure, and enhancement pattern, are different among the genetic subtypes of glioma.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular features have also been added to the grading along with the previously used histopathological characteristics [ 18 ]. Over the years, different imaging modalities such as diffusion-weighted imaging (DWI), and dynamic contrast-enhanced MRI have also been studied for their potential use in tumor grading [ 19 , 20 ]. More recently, great interest has been taken in studying high-grade and low-grade tumor characteristics using DTI.…”
Section: Discussionmentioning
confidence: 99%